Developing COVID-19 digital comic by using flip pdf professional as a learning media for tenth grade of senior high school - Akhmad Syaferi; Nasrul Hakim; Yudiyanto Yudiyanto; Suhendi Suhendi (Assimilation: Indonesian Journal of Biology Education, 2022)
The development of learning media in the form of COVID-19 digital comics using Flip PDF Professional is based on the background that the learning media used by SMA Negeri 2 Sekampung teachers are still in the form of textbooks and powerpoints, and there are still many students who do not understand the virus and educational material related to COVID-19, so it is necessary to develop a learning media innovation in the form of COVID-19 digital comics to make learning fun and not boring by combining viral material. Comics were chosen because its presentations are interesting, simple and have a storyline which contains complex messages and information. It can be presented briefly and equipped with communicative language that is dialogic and easy to understand by readers. This study aims to develop a COVID-19 digital comic learning media for tenth grade senior high school students. The method used in this study is research and development with the ADDIE development model which consists of five stages, namely analyze, design, development, implementation and evaluation. The results of product validation developed have been declared "very feasible" to be tested by validators, namely material expert validators and media experts, while the results of product trials developed have been declared "very good" by teachers and students, so that learning media in the form of digital comics can be used as an alternative learning media in the classroom.